Surgical Management of Simultaneous Anterior Cruciate Ligament and Patellar Tendon Ruptures: A Systematic Review - Meheux, Carlos J.; Jack, Robert A., II; McCulloch, Patrick C.; Lintner, David M.; Harris, Joshua D. (The Journal of Knee Surgery, 2018)
This study performs a systematic review to determine (1) if a significant difference exists in return to preinjury activity level between one- and two-stage treatment of combined anterior cruciate ligament (ACL) and patellar tendon (PT) tears; and (2) if a significant difference exists in the number of postoperative complications between the two differing surgical treatment approaches. A systematic review was performed using Preferred Reporting Items for Systematic reviews and Meta-Analyses (PRISMA) guidelines and registered on PROSPERO. MEDLINE, Cochrane Central Register of Controlled Trials, SCOPUS, and Sport Discus were searched for English language level I–IV evidence studies on either one- (simultaneous) or two-stage (sequential) surgical treatment of simultaneously sustained ipsilateral ACL and PT tears. The approach to initial evaluation, diagnosis, treatment, and outcomes were qualitatively analyzed. Methodological quality assessment of all included studies was completed using the Methodological Index for Non-randomized Studies (MINORS). The Grading of Recommendations, Assessment, Development, and Evaluation (GRADE) tool was used to assess quality of evidence and provide strength of recommendation. Statistical analyses were done using Fischer's exact test. Eleven articles (18 patients; 83% males; mean age, 31.1 ± 10.1 years; mean follow-up, 2.2 ± 1.7 years; and mean MINORS 7.8/16) were analyzed. Eight patients had a one-stage procedure (primary PT repair and ACL reconstruction), and 10 patients underwent a two-stage procedure (primary PT repair first followed by ACL reconstruction) with mean 28 ± 45.7 weeks (5 weeks–3 years) between surgeries. The rate for return to preinjury activity level after surgery was not significantly different between one- (88%) and two-stage (100%) (p = 0.444). There was a significantly higher complication rate (p = 0.023) in the one-stage (stiffness, instability, and patella baja) versus two-stage surgery (no complications). There was no significant difference in return to preinjury activity level between one- and two-stage PT repair and ACL reconstruction. However, the one-stage combined surgery had a significantly higher complication rate compared with two-stage surgery. The level of evidence is IV.
Keywords: anterior cruciate ligament; patella tendon; rupture; simultaneous